ANALISIS KEBERHASILAN PEMBERDAYAAN PETANI MELALUI OEMAH PINTAR PETANI DI KELURAHAN KANDRI KECAMATAN GUNUNGPATI KOTA SEMARANG - Muhammad Dian Rifqi; Nina Widowati; Budi Puspo Priyadi (Journal of Public Policy and Management Review, 2023)
Oemah Pintar Petani is a non-governmental organisation (NGO) in Kandri Village, Gunungpati Subdistrict, Semarang City that oversees the field of agricultural education. Oemah Pintar Petani functions as an empowerment platform for farmer groups, an agricultural education tourism destination for the community, and an independent economic area for Kandri Tourism Village. The purpose of this study is to determine the Empowerment of Oemah Pintar Petani and analyse the achievements that have been achieved by Oemah Pintar Petani in increasing community empowerment in Kandri Village, Gunungpati District, Semarang City. The research method used by researchers is a mix method (mixed method) used is embedded design. This research focuses on descriptive qualitative data as primary data and quantitative as secondary data by collecting data using interviews with farmers, administrators, and programme members. The analysis technique used is data reduction carried out on qualitative data, data presentation and coding used on quantitative data, and conclusion drawing. The results show that Oemah Pintar Petani has succeeded in bringing about positive changes in accordance with the principles of empowerment. In overcoming the decline in the number of active farmers, the programme empowers farmers through increasing knowledge and skills, which is a central aspect of empowerment theory, seen from the survey that reached 92% success rate, confirming that the provision of knowledge and skills has turned farmers into agents of change in agriculture.